Assessment of Efficiency of an Indigenous Liquid Smoke for masmin Production - Nithin, C. T.; Yathavamoorthi, R.; Niladhri, S. C.; Ananthanarayanan, T. R.; Suseela, M.; Bindu, J.; Gopal, T. K. S. (Fishery Technology, 2025)
The aim of this study was to develop a methodology for the production of liquid smoke from coconut husk and to evaluate efficiency of the same in masmin production. The developed method can produce 1.5 l of liquid smoke per hour. It had total phenolic content of 1348 ppm and carbonyl content of 38.03 mg ml-1. Titratable acidity and pH were found to be 1.88% by weight of acetic acid and 4.34, respectively. Total PAH content in the liquid smoke was found to be 0.79 ppb of which phenanthrene was found in highest level (0.54 ppb). Benzo[a]pyrene was not detected. The developed liquid smoke was found to be compliant with current regulatory limits in terms of PAH. It was observed that soaking of cooked skipjack tuna loins in liquid smoke added with 5% salt, for a duration of 30 min produced masmin with similar flavour of traditional masmin.